2002
DOI: 10.3732/ajb.89.7.1164
|View full text |Cite
|
Sign up to set email alerts
|

Floral biology and unique pollination system of root holoparasites, Balanophora kuroiwai and B. tobiracola (Balanophoraceae)

Abstract: We investigated the floral and pollination biology of two monoecious root holoparasites, Balanophora kuroiwai and B. tobiracola (Balanophoraceae), in the subtropical forests of southern Japan. Both species secrete nectar from extrafloral nectaries distributed among the flowers, which is mainly consumed by ants, cockroaches, and pyralid moths. Pollen grains were found attached to the bodies of these insects. Pyralid moths of the genera Assara and Nacoleia were observed laying eggs on the inflorescences of B. ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 34 publications
1
31
0
2
Order By: Relevance
“…Another possibility is that Oecophylla itself is a pollinator particularly mediating selfing, as has been suggested in other ant‐plant associations (e.g. Kawakita & Kato 2002; Raju & Ezradanam 2002). Future studies should test this hypothesis, although literature suggests this unlikely, because ants often damage pollen activities by their external glands secretions (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…Another possibility is that Oecophylla itself is a pollinator particularly mediating selfing, as has been suggested in other ant‐plant associations (e.g. Kawakita & Kato 2002; Raju & Ezradanam 2002). Future studies should test this hypothesis, although literature suggests this unlikely, because ants often damage pollen activities by their external glands secretions (e.g.…”
Section: Discussionmentioning
confidence: 85%
“…In the latter case, excluding insects only had a significant effect on fruit set if the male and female plants were close together, which matches expectations of ant behaviour. In the Ryukyu archipelago, selective exclusion experiments showed that ants were capable of pollination within inflorescences of Balanophora kuroiwai, a low-growing parasitic herb, but they were not observed to move between inflorescences (Kawakita & Kato, 2002).…”
Section: (4 ) Hymenopteramentioning
confidence: 99%
“…In the three ant genera recorded in this study, Nylanderia are known as pollinators of the plants Petrosavia sakuraii (Petrosaviaceae) (Takahashi et al. ), Balanophora tobiracola (Balanophoraceae) (Kawakita & Kato ) and Jatropha curcas (Euphorbiaceae) (Luo et al. ).…”
Section: Discussionmentioning
confidence: 99%